Rainbows in Eastern African folktales: Oral narrative as ecocritical model - Inge Brinkman; Teshome Mossissa; Peter Wasamba; James Wachira (Tydskrif vir letterkunde, 2025)
The rainbow makes for strong imagery: throughout world history, the rainbow has functioned in many ways as a tool to think with. This is no different in African contexts. Our aim in this paper is to explore the changing meanings given to relations between rainbows and snakes in narratives from the Gikuyu language in Central Kenya. We thereby remain open to the wider East African context, indicating the multiple meaning-making of rainbows in ecological terms. This diachronic approach to narratives allows us to show how rainbow imagery formed a model that interpreted human/nonhuman relations long before the current global ecological crisis was recognised in developmental circles. In our narrative analysis, we argue that connections were drawn between rainbows and snakes, and in turn between humans and entities like rainbows and snakes. The moral evaluation of rainbow-snakes was ambivalent: they could be dangerous, and they could be good; they could be destructive, and they could be enabling. Analysing the narratives left us with a new perspective on the evaluation of human characters and the rainbow-snake: it could treat humans badly, but humans could also treat the rainbow-snake badly. We furthermore show that in the course of the colonial era, this symbolism changed, and the rainbow-snake as an ecocritical model disappeared in the process: the connection between snake and rainbow disappeared, and the ambivalence of the imagery got lost. Good and bad became clearly distinguishable and inherent: it no longer depended on the way of interacting with the entity. Our diachronic interpretation does not form a call to do away with current images and go back to an assumed romantic, pristine African past. Yet it may be wise to reflect on what imaginative history can teach us, and to learn from narratives in history as a way to overcome the exclusive focus on logical-scientific thinking, arriving at a less anthropocentric interpretative model through narrative thinking. Our analysis points out that these East African oral narratives may be instructive in the context of the current global ecological crisis.